Combinations of proinflammatory cytokine genes and their interactions in Russian tuberculosis patients in the Chelyabinsk Region - S. V. Belyaeva; D. S. Stashkevich; A. L. Burmistrova (Медицинская иммунология, 2020)
Tuberculosis is a widespread infectious disease caused by M. tuberculosis, which is one of the leading causes of death  in the world.  According to numerous literature data,  this is a genetically determined disease, and genetical polymorphism is a mechanism that leads to progression from infection to clinical  manifestation. Susceptibility to infection correlates with different genes at several loci, and each individual gene plays a unique role. It is known, that  the analysis of individual polymorphic variants  of genes does not provide  a sufficiently complete picture of the  mechanisms of formation of a predisposition to multifactorial pathologies, such  as tuberculosis, since  their  development is based  on complex intergenic and  gene-environmental interactions, which  must  be taken  into  account when  predicting the  risk of developing active  forms of the  disease  and  its severity. The concept of the functioning of cytokines as biomarkers of tuberculosis suggests that their products and interactions play an important role in the immunopathogenesis of the disease, because they form a cytokine chain  with  unique  functions, where  the  removal  of any  link in the  chain  disrupts  the  entire  mechanism of the  immuno-inflammatory process.  IL-6, together with  TNFα and  IL-1β, initiate early  pro-inflammatory reactions in  tuberculosis, stimulating local  and  systemic  inflammatory reactions under  participation of all common pro-inflammatory mechanisms with further  transition to activation of acquired immunity. Earlier, we carried  out a set of studies to evaluate  the association of alleles and genotypes  of these cytokine genes with a predisposition/resistance to pulmonary tuberculosis in Russians  of the  Chelyabinsk region.  These  studies have resulted  into assessment of certain distribution patterns of IL-1β, TNFα, IL-6  alleles and their genotypes in pulmonary tuberculosis and its various clinical  forms. The following methods were used: isolation of DNA samples  from whole blood,  genotyping of the studied  gene polymorphisms using PCR  and RFLP techniques. In this study, we analyzed  the intergenic interactions of the genes for the pro-inflammatory cytokines IL-1β, TNFα, IL-6 using the method of reducing multifactor dimension in patients with pulmonary tuberculosis. The program designs optimal models  of combinations for the studied  genes and their  interactions in tuberculosis patients. As a result of this study, a three-locus model  IL-6  (-174)*С – IL-1β (+3953)*Т – IL-1β (+3953)*С was established, which was characterized by 100% reproducibility and prediction accuracy of 72%. Among the analyzed  polymorphisms, the  IL-6  (-174)*C polymorphism possessed  the  highest  predictive potential with 15.27%.